First Record of Phoretic Mite from Red Palm Weevil Rhynchophorus ferrugiuneus (Olivier,1790) from Basrah, Southern Iraq - Abdullah Najim, Shurooq; Hussain Ali Jabbar; Basil Yousuf Mahdi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The red palm weevil Rhynchophorus ferrugineus (Olivier, 1790), which belongs to the family Curculionidae, order Coleoptera, is one of the most important palm pests, which leads to heavy losses in date palms. In the last few years, it has been recorded in Iraq, from Safwan city south of Iraq, where it was detected on date palm trees (Phoenix dactylifera L, Arecales: Arecaceae). In the current study, specimens of adult weevils were collected from infested date palms (Phoenix dactylifera), that showed signs of infection in Safwan district, south of Basra province. The results of the investigation showed the presence of phoretic mites associated with the red palm weevil Rhynchophorus ferrugineus (Olivier, 1790). Two genera of Uropodid mites, deutonymph, were attached by anal pedicel to body parts of adult red palm weevils. They were collected and identified as Centrouropoda (Uropodidae), and Uroovbovella (Urodinychidae), according to accurate taxonomic keys. The differentiation between two genera of mites was studied. The deutonymphs were examined and photographed by an AM Scop camera installed on a light microscope, and the insects were photographed by a LEICA microscope. The infestation symptoms were illustrated with pictures.